Pembuatan dan Analisis Eco Enzyme dengan Memanfaatkan Limbah Rumah Tangga (Kulit Pisang, Kulit Buah Naga, Kentang, Wortel Dan Jagung) - Meika Hikmatriana; Nadia Fitra Firnadi; Nisa Nurhidayanti (Prosiding Sains dan Teknologi, 2022)
Waste is still a serious problem in Indonesia. How to manage waste in the community environment refers to the end of pipe method (final approach). Waste management with the end of pipe method can be replaced in a new way, namely by managing waste earlier. Eco enzyme or eco enzyme in Indonesian is a solution of complex organic substances produced from the fermentation process of organic waste, sugars, and water. Waste processing with the Eco enzyme method uses the fermentation method (Bernadin, Desmintari, and Yuhanijaya 2017). This eco enzyme is made with the basic ingredients of kitchen waste which includes fruit and vegetable skins and then mixed with brown sugar (mollase) and water in a ratio of 3: 1: 10. In this study, there were five Eco Enzyme variables with different compositions, namely by using banana peel components, dragon fruit peels, potatoes, corn, and carrots. The results showed that the fermentation of eco enzyme solutions made from banana peels, dragon fruit peels, potatoes, corn, and carrots had acidic properties with a pH of 3.5, TDS 1460, and a moisture content of 93%. Visually, the resulting solution is brownish in color, the smell smells freshly typical of fermented aromas, and is produced by mama enzymes in eco enzymes, as well as the absence of contamination such as insects or other animals. Keywords: Waste, Eco Enzyme, Fermentation